2014
DOI: 10.1007/s10803-014-2201-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Visual Activity Schedules as Evidence-Based Practice for Individuals with Autism Spectrum Disorders

Abstract: A comprehensive review of the literature was conducted for articles published between 1993 and 2013 to evaluate the quality of the Visual Activity Schedules (VAS) literature using current evidence-based criteria developed by Horner et al. (Except Child 71:165-179, 2005). Authors sought to determine whether VAS can be considered an evidence-based practice by expanding on the findings from previous reviews. A total of 31 studies met inclusion criteria for the use of VAS to various behaviors to students with auti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
88
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(100 citation statements)
references
References 44 publications
6
88
0
6
Order By: Relevance
“…Visual schedules are used to orientate students and provide predictability within the classroom by informing students of an anticipated sequence of events using pictures, symbols and/or written language. Making transitions predictable is thought to reduce anxiety for individuals on the autism spectrum (Sterling‐Turner and Jordan, ), and is associated with reductions in problem behaviour (Knight, Sartini and Spriggs, ). The National Autism Center () lists ‘schedules’ as ‘established interventions’ indicating that they are useful in promoting independence and helping students to plan.…”
Section: Structured Teachingmentioning
confidence: 99%
See 2 more Smart Citations
“…Visual schedules are used to orientate students and provide predictability within the classroom by informing students of an anticipated sequence of events using pictures, symbols and/or written language. Making transitions predictable is thought to reduce anxiety for individuals on the autism spectrum (Sterling‐Turner and Jordan, ), and is associated with reductions in problem behaviour (Knight, Sartini and Spriggs, ). The National Autism Center () lists ‘schedules’ as ‘established interventions’ indicating that they are useful in promoting independence and helping students to plan.…”
Section: Structured Teachingmentioning
confidence: 99%
“…Wong, Odom, Hume, et al. () similarly categorise ‘visual supports’, including schedules, as an evidence‐based practice, and a review by Knight, Sartini, and Spriggs () concluded that visual schedules were effective in promoting on‐task behaviour and facilitating independent transitions. Together, these reviews indicate that visual schedules are an effective way to support students on the spectrum.…”
Section: Structured Teachingmentioning
confidence: 99%
See 1 more Smart Citation
“…To be considered evidence-based, a practice must have at least five studies, conducted by different researchers, in different locations, with a minimum of 20 participants over all of the studies (Horner et al, 2005). It was determined that visual supports were an evidence- Instruction, January 2018 • Vol.11, No.1 based practice and can be used for a variety of different behaviours (Knight, Sartini, & Spriggs, 2015).…”
Section: Visual Supportsmentioning
confidence: 99%
“…Lequia, Machalicek, and Rispoli (2012) conducted a systematic review, focusing on problem behaviors in relation to di erent variables. Knight, Sartini, and Spriggs (2015) evaluated the quality of the activity schedule literature using evidence-based criteria.…”
Section: Introductionmentioning
confidence: 99%